Uncovered fields : perspectives in First World War studies - Macleod, Jenny; Purseigle, Pierre (History of warfare ;, 2004)
This work presents research on the military, social, and cultural history of World War I. It explores the stresses of waging a war, whose "totalizing logic" issued formidable challenges to communities, and accounted for the pervasion of the conflict into the private sphere.